2020
DOI: 10.21203/rs.3.rs-100956/v3
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Efficacy and Safety of Ivermectin for Treatment and prophylaxis of COVID-19 Pandemic

Abstract: Background: Up-to-date, there is no recognized effective treatment or vaccine for the treatment of COVID-19 that emphasize urgency around distinctive effective therapies. This study aims to evaluate the anti-parasitic medication efficacy "Ivermectin" plus standard care in the treatment of mild/moderate and severely ill cases with COVID 19 infection, as well as prophylaxis of health care and/ or household contacts.Subject and methods: 600 subjects; 400 symptomatic confirmed COVID-19 patients and 200 health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 6 publications
1
50
0
Order By: Relevance
“…After excluding 52 duplicates, 341 titles and abstracts were screened. Full-text articles for the remaining 33 records were retrieved, of which two were excluded for testing the drug for COVID-19 prophylaxis; [ 42 , 43 ] four for retraction [ 21 24 ], two due to the study design (not RCT) [ 44 , 45 ], one for including children [ 46 ], and one for a too short follow-up, having not assessed patients until recovery or death [ 47 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After excluding 52 duplicates, 341 titles and abstracts were screened. Full-text articles for the remaining 33 records were retrieved, of which two were excluded for testing the drug for COVID-19 prophylaxis; [ 42 , 43 ] four for retraction [ 21 24 ], two due to the study design (not RCT) [ 44 , 45 ], one for including children [ 46 ], and one for a too short follow-up, having not assessed patients until recovery or death [ 47 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The need for evidence synthesis is imperative for medical doctors and the community. Systematic reviews have been published on the topic, but in the majority of them a retracted trial represented more than 10% of the overall effect, [ 20 , 21 , 27 , 28 ] which overestimated the benefits. One of those was recently reassessed after the exclusion of this trial, which changed the results from reducing mortality to lack of benefit in this outcome [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include (i) Nucleic acid vaccines as mRNA-based-vaccines such as Moderna (Mahase 2020), BioNTech/Pfizer (Müller et al 2021) (Palacios et al 2020) developed by China Sinovac biotech company; (iv) Antigen-based vaccine EpiVacCorona that was developed by the Vector Institute (Ryzhikov et al 2021). On the other hand, the treatments suggested for COVID-19 are limited to those either still in clinical trials such as favipiravir (Pilkington et al 2020), ribavirin (Khalili et al 2020), lopinavir-ritonavir (Dalerba et al 2020), emetine (Choy et al 2020), hydroxychloroquine (Chen et al 2020a), methionine (Zhang et al 2020), homoharringtonine and ivermectin (Elgazzar et al 2020) or initially approved by U.S. FDA such as remdesivir (Beigel et al 2020). Furthermore, CR3022 monoclonal antibody with binding affinity to the RBD of SARS-CoV-2 S protein was suggested as a therapeutic approach .…”
Section: Introductionmentioning
confidence: 99%
“…In a study from Egypt which included 400 patients with confirmed COVID-19 patients with mild/moderate and severe COVID-19 who were treated with ivermectin plus standard of care (azithromycin, vitamin C, zinc, lactoferrin, acetylcysteine and prophylactic or therapeutic anticoagulation) had lower mortality rate (0% and 2%, respectively) in comparison to patients who received hydroxychloroquine and standard of care (4% and 20%, respectively). Also, they had substantial improvement in laboratory parameters one week after treatment (p<0.001) [73] . A retrospective study of 280 patients hospitalized due to COVID-19 showed lower mortality in patients who were treated with ivermectin (15.0% vs. 25.2%; OR, 0.52; 95% CI, 0.29-0.96; P = 0.03).…”
Section: Corticosteroids -Benefit Demonstratedmentioning
confidence: 94%